2015
DOI: 10.1016/j.jcat.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of ethane with CO2 over supported Au

Abstract: Reaction of C 2 H 6 with CO 2 Au catalyst Effects of supports Electronic interaction between Au and oxides a b s t r a c tThe dehydrogenation of C 2 H 6 and its reaction with CO 2 have been investigated on Au deposited on various oxides. Both reactions occurred at relatively high temperatures, above 650 K. Ethylene formed in the dehydrogenation process with high selectivity, 94-98%, on most of the catalysts. The conversion of C 2 H 6 varied with the nature of support and fell in the range of 3-19%. Adding CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…As was discovered by several decades ago, Au in nanosize exhibits a surprisingly high activity in many catalytic reactions [16][17][18]. Recently, we found that Au nanoparticles supported by n-type semiconducting oxides are very effective catalysts in the reaction of C 2 H 6 with CO 2 [19].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…As was discovered by several decades ago, Au in nanosize exhibits a surprisingly high activity in many catalytic reactions [16][17][18]. Recently, we found that Au nanoparticles supported by n-type semiconducting oxides are very effective catalysts in the reaction of C 2 H 6 with CO 2 [19].…”
Section: Introductionmentioning
confidence: 82%
“…It has been demonstrated in several studies that negatively charged CO 2 is much more reactive than the neutral one [28,29]. Recently, it was reported that n-type oxidic supports for Au are much more efficient in the reaction between CO 2 and C 2 H 6 compared to Au samples deposited on insulating oxides [19].…”
mentioning
confidence: 99%
“…Nevertheless, these kinds of catalysts are still limited by the drawbacks of environmental hostility, relatively low selectivity or poor long-term stability. Recently, the reaction between ethane/propane and CO 2 has been studied on Au-based catalysts [12,13]. Dry reforming as well as oxidative dehydrogenation can occur over these supported Au catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic reaction was followed in the same way as described in our previous paper [7]. The reactor was equipped with a 500 W medium pressure mercury vapor lamp (TQ 718, Heraeus Noble light, Germany) as a light source.…”
Section: Methodsmentioning
confidence: 99%
“…of dimethyl ether [16], in the reaction of ethane with CO 2 [7], in the hydrogenation of CO 2 [20], and in the production of H 2 in the photocatalytic reactions of ethane [15].…”
Section: Introductionmentioning
confidence: 99%